Response and shear mechanism of RC bridge piers confined with CFRP grid-reinforced ECC subjected to truck collision. (January 2023) - Zhou, Chang; Wang, Wenwei; Zheng, Yuzhou; Cheng, Yi; Wu, Zenghan
Highlights: Intensive numerical simulations are performed to investigate the failure process of CFRP grid-reinforced ECC confined RC bridge piers under truck collision. CFRP grid-reinforced ECC will significantly decrease the tension stress of longitudinal reinforcements, CFRP grids and stirrup hoops can work simultaneously to improve the dynamic shear resistance of confined bridge piers. Two equations are proposed to calculate the dynamic shear demand of trucks and dynamic shear capacity of CFRP grid-reinforced ECC confined bridge piers. Shear mechanism of CFRP grid-reinforced ECC confined piers is clarified. Abstract: To improving the impact resistance of RC bridge piers under truck collision, numerical simulation is carried out to compare the dynamic response of reinforced concrete (RC) piers and carbon fiber reinforced polymer (CFRP) grid-reinforced engineered cementitious composites (ECC) confined RC piers. Parametric analysis is conducted to investigate the effect of ECC and CFRP on the dynamic shear capacity of bridge piers. Numerical results show that the presence of CFRP grid-reinforced ECC will decrease the tension stress of longitudinal rebars. Besides, CFRP can work simultaneously with stirrup hoops to improve the shear resistance of confined piers. The quantitative analysis indicates that CFRP and ECC have significant influence on improving the dynamic shear capacity of bridge piers, while weight of engine and initial velocity of truck are the predominate factors of dynamic shear demand. Finally, two formulae for predicting dynamic shear demand of trucks and shear capacity of composite bridge piers are proposed, and the shear mechanism of confined piers is clarified.